Discovery of Coumarin as Microtubule Affinity-Regulating Kinase 4 Inhibitor That Sensitize Hepatocellular Carcinoma to Paclitaxel - Shen, Xianyan; Liu, Xuesha; Wan, Shunli; Fan, Xin; He, Huaiyu; Wei, Rong; Pu, Wenchen; Peng, Yong; Wang, Chun (Frontiers in Chemistry, 2019)
Hepatocellular carcinoma (HCC) is one of the most prevalent cancers worldwide. Nowadays, pharmacological therapy for HCC is in urgent needs. Paclitaxel is an effective drug against diverse solid tumors, but commonly resisted in HCC patients. We recently have disclosed that microtubule affinity-regulating kinase 4 (MARK4) increases the microtubule dynamics and confers paclitaxel resistance in HCC, suggesting MARK4 as an attractive target to overcome paclitaxel resistance. Herein, we synthesized and identified coumarin derivatives 50 as a novel MARK4 inhibitor. Biological evaluation indicated compound 50 directly interacted with MARK4 and inhibited its activity in vitro, suppressed cell viability and induced apoptosis of HCC cells in a MARK4-dependent manner. Importantly, compound 50 significantly increased the drug response of paclitaxel treatment to HCC cells, providing a promise strategy to HCC treatment and broadening the application of paclitaxel in cancer therapy.